Perception of the Nordic Countries : China survey - Spaven, Patrick (Copenhagen : Nordic Council of Ministers, 2008)
Increasing globalization is making the world smaller. The Nordic countries and their companies can benefit from this by exploring new markets. One of the most important markets to get established on is the Chinese, the biggest market in the world. In connection with the upcoming Worlds Exposition, EXPO 2010, hosted by the Chinese city of Shanghai, the Nordic council of Ministers has ordered a survey on the opinions and attitudes in China towards the Nordic Countries, Sweden, Norway, Finland, Denmark, and Iceland. The report is devised with the purpose of providing the countries and the Nordic council of Ministers with a tool to help plan their activities at EXPO 2010. The report emphasises on a range of different variables that shows the Chinese´ general positive assumption of the Nordic Countries especially on quality of life, public service, social environment, and economic achievements.